AGRIBISNIS KELADI DI KEPENGHULUAN DARUSSALAM KECAMATAN SINABOI KABUPATEN ROKAN HILIR - Yuliansyah Putra; Eliza Eliza; Ermi Tety (Fakultas Pertanian, Universitas Riau, 2021)
This study was aims to determine the agribusiness taro in Darussalam Village District Sinaboi Rokan Hilir Regency. This research was conducted in Darussalam Village, Sinaboi District, Rokan Hilir Regency by using survey method. The technique of taking respondents is done by purposive sampling. The results showed that the total production cost of taro farming in one season in Darussalam village was Rp 9.431.770/ha. Average taro yield of 7.052 Kg/ha/MT resulted in net income or farming profit of taro average Rp 13.134.630, -/ha/MT. These results indicate that taro farm in Darussalam Village is efficient and feasible to be continued as indicated by Return Cost Ratio (RCR)> 1 (2.41). Farmers harvest handling is only collecting, sorting and transporting activities whereas the transportation is not done by farmers. The marketing channel of taro in Darussalam village there is only one marketing channel that is from farmer to tauke. Supportive institutional subsystems are farmer group institutions, capital lending institutions, agricultural extension agencies, and government agencies, but not all of them have worked well.